2020
DOI: 10.1016/j.nmd.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory muscle strength training improves measures of pressure generation and cough strength in a patient with myotonic dystrophy type 1

Abstract: Expiratory muscle strength training (EMST) exercise programmes aim to improve respiratory function by increasing the force generating capability of expiratory muscles by resistance training. In neuromuscular conditions, in which cough flow generation is often decreased, there is increasing interest in EMST as a therapeutic intervention. We present data showing efficacy of EMST in a patient with adult onset Myotonic Dystrophy Type 1 (DM1). A domiciliary training programme (5 days per week over 32 weeks) resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Both MIP and SNIP assess inspiratory muscle strength, but in the current study IMT only showed an improvement of MIP. This is in contrast with previous studies reporting an effect of respiratory muscle training on SNIP [40,48,49]. SNIP evaluates diaphragm strength more specifically than MIP, as demonstrated in previous studies where SNIP generated higher transdiaphragmatic pressures than MIP [50,51].…”
Section: Discussioncontrasting
confidence: 73%
“…Both MIP and SNIP assess inspiratory muscle strength, but in the current study IMT only showed an improvement of MIP. This is in contrast with previous studies reporting an effect of respiratory muscle training on SNIP [40,48,49]. SNIP evaluates diaphragm strength more specifically than MIP, as demonstrated in previous studies where SNIP generated higher transdiaphragmatic pressures than MIP [50,51].…”
Section: Discussioncontrasting
confidence: 73%
“…Another case study investigated 32 weeks of expiratory respiratory training with a patient with myotonic dystrophy type-1 (Table 1) [12]. Improvements in expiratory mouth pressure and peak cough flow, along with maximum inspiratory and sniff nasal pressures were observed.…”
Section: Respiratory Managementmentioning
confidence: 99%